Synchronous Mindfulness in Motion Online: Strong Results, Strong Attendance at a Critical Time for Health Care Professionals (HCPs) in the COVID Era - Klatt, Maryanna; Bawa, Rani; Gabram, Olivia; Westrick, Alexis; Blake, Amanda (Frontiers in Psychology, 2021)
Mindfulness in Motion (MIM) is an organizationally-sponsored mindfulness program for employees at a large academic health center that consistently produces significant reductions in burnout and perceived stress, alongside significant increases in work engagement and resilience. This study compared outcome measures of a synchronous virtual delivery of MIM, necessitated by COVID-19, to traditional in-person delivery of MIM. Outcome measures from the virtual COVID (AU20, WI21, SP21) MIM cohorts (n= 99) were compared with the in-person Pre-COVID (SP19, AU19, WI20) MIM cohorts (n=124). Both Pre-COVID and COVID cohorts had similar attendance rates with an average attendance of 84% and 80% respectively. Qualitative analysis of COVID cohorts reported community support during COVID as a substantial intervention benefit, which was important at a time when isolation dominated the healthcare professional experience. Total burnout was determined by scores on the subscales of the Maslach Burnout Inventory (MBI). There were no significant differences in depersonalization (p=0.3876) and personal accomplishment (p=0.1519) changes between Pre-COVID and COVID cohorts, however there was a significant difference in emotional exhaustion (p=0.0315), with COVID cohorts improving more. The Connor Davidson Resiliency Scale (CDRS) and Utrecht Work Engagement Scale (UWES) also produced no significant differences between groups (p=0.4259, p=0.1984, respectively). The Perceived Stress Scale (PSS) though yielded significant differences in reduction between groups (p=0.0405), again with COVID cohorts showing greater improvement. Results of the first synchronous, virtually-delivered MIM cohorts demonstrate participants achieved similar results and MIM created a community in a time when it was greatly needed due to pandemic healthcare professional stress.